Fault geometry and kinematics at the intersection of the Zemuhe, Daliangshan and Xiaojiang Faults - Wang, Mingming; Wei, Zhanyu; Long, Feng; Chen, Han; Li, Sheng (Frontiers in Earth Science, 2024)
The complexity of strike-slip fault segmentation affects the initiation, propagation, and termination of earthquake ruptures and the earthquake magnitude. Studying the fault geometry, kinematics, and segmentation provides fundamental knowledge for mitigating earthquake hazards along faults. The Zemuhe, Daliangshan, and Xiaojiang Faults intersect along the eastern boundary of the Tibetan Plateau in the area from Ningnan in Sichuan Province to Qiaojia in Yunnan Province. Although few large earthquakes have occurred on these faults, the relationships between the intersections of these three faults and earthquake rupture behavior in this region are poorly constrained. The interpretation of aerial photographs and detailed field surveys revealed the geometric pattern and fault kinematics in the area of intersection. The distribution patterns and focal depths near the faults were obtained via analysis of seismic data in the area of intersection. The northern segment of the Xiaojiang Fault deviates approximately 25° northwest of Qiaojia, forming a conspicuous bend. The Xiaojiang Fault continues to extend southeast of the Ningnan Basin, where it intersects with the southern segment of the Zemuhe Fault, forming a pull-apart basin approximately 4.5 km wide. The bend and Ningnan pull-apart basin mark the segmented boundary between the Zemuhe Fault and the Xiaojiang Fault, which may prevent the propagation of large earthquake ruptures along the eastern boundary fault. Moreover, the lack of obvious geometric complexity between the Daliangshan Fault and Xiaojiang Fault might hinder the prevention of earthquake rupture propagation. Additionally, our results suggest that different earthquake prevention and disaster reduction measures should be taken for different cities in the region.